(untitled) (The Pakistan Development Review, 2004)
The paper analyses the implications of a subsidy policy on education and of different liberalised trade and investment policies on the incidence of child labour in a developing economy in terms of a three-sector general equilibrium model with informal sector and child labour. The supply function of child labour is endogenously determined. The paper shows that different policies, if undertaken concurrently, may produce mutually contradictory effects, thereby producing little or no impact on the incidence of child labour. The paper provides a theoretical answer as to why the incidence of child labour has not significantly declined in the developing economies in spite of economic development and globalisation.